EFEKTIVITAS PENCAPAIAN AKUNTABILITAS PUBLIK DAN PENGELOLAAN SUMBERDAYA ORGANISASI DALAM MENINGKATKAN KINERJA ORGANISASI DI PEMERINTAH KABUPATEN CILACAP - Sutarjo Sutarjo (Jurnal Good Governance, 2018)
The purpose of this study is to determine the influence of the effectiveness of public accountability achievement of government institution and organizational resource management on the level of success in achieving the performance of the organization or government agency. The hypothesis of this research is there is a positive influence between the effectiveness of achieving public accountability and the effectiveness of resource management on high performing organizations in the cilacap regency government. data analysis techniques use simple linear regression and multiple linear regression. hypothesis test using formula F and coefficient of determination. The results showed there is a positive influence between the effectiveness of public accountability achievement and effectiveness of resource management to high performance organizations in government of Cilacap regency, Recommendations of research are: Improvement of organization performance is done through intensive supervision from OPD leader related to execution of duty and function of OPD.The setting of realistic and objective target indicators; increase self-belonging and responsibility from the member of organizations.Keywords: organization’s performance, public accountability, resource management.